Application of ImageJ program to the enumeration of Orientia tsutsugamushi organisms cultured in vitro - Siritantikorn, S; Jintaworn, S; Noisakran, S; Suputtamongkol, Y; Paris, D; Blacksell, S (2012)
The ImageJ program was applied to the enumeration of Orientia tsutsugamushi organisms in cell culture using indirect immunofluorescence assay (IFA). The highest correlation (r = 0.984) was observed between manual counting methods and the ImageJ program (MaxEntropy threshold algorithm). This software-based methodology is cheaper, more standardised and better reproducible than a manual-based approach. © 2012 Royal Society of Tropical Medicine and Hygiene.